1985
DOI: 10.1128/mcb.5.9.2332
|View full text |Cite
|
Sign up to set email alerts
|

Transcription boundaries of U1 small nuclear RNA.

Abstract: Transcription-proximal stages of Ul small nuclear RNA biosynthesis were studied by 32p labeling of nascent chains in isolated HeLa cell nuclei. Labeled RNA was hybridized to nitrocellulose-immobilized, single-stranded M13 DNA clones corresponding to regions within or flanking a human Ul RNA gene. Transcription of Ul RNA was inhibited by >95% by at-amanitin at 1 ,ug/ml, consistent with previous evidence that it is synthesized by RNA polymerase II. No hybridization to DNA immediately adjacent to the 5' end of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
39
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 54 publications
3
39
0
Order By: Relevance
“…The small nuclear RNAs, including Ul and U2, rely directly on transcription termination as the first step in the formation of their respective 3' ends (1,5,20,21,25,44). This direct termination-3' end formation mechanism contrasts with 3' end formation in mRNAs.…”
mentioning
confidence: 94%
“…The small nuclear RNAs, including Ul and U2, rely directly on transcription termination as the first step in the formation of their respective 3' ends (1,5,20,21,25,44). This direct termination-3' end formation mechanism contrasts with 3' end formation in mRNAs.…”
mentioning
confidence: 94%
“…The biosynthesis of snRNPs is itself complex, with several features different from mRNA transcription and processing. U1, U2, U4, and U5 RNAs are transcribed by polymerase II but, unlike most polymerase II transcripts (mRNA), are capped with trimethylguanosine (Ro-Choi et al 1976;Jensen et al 1979;Roop et al 1981;Kunkel and Pederson 1985). We and others have recently demonstrated that U6 RNA is transcribed by a different enzyme which, by the criteria of ~-amanitin sensitivity and competition for 5S gene transcription machinery, is likely to be RNA polymerase III (Kunkel et al 1986;Reddy et al 1987).…”
mentioning
confidence: 99%
“…Two pieces of evidence now indicate that the 3' ends of the snRNA precursors are formed by either termination of transcription or an RNA processing event directly coupled to transcription. First, run-on transcription in isolated nuclei does not proceed further than 60 nt beyond the 3' end of the mature Ul snRNA (24). Second, 3'-end formation of Ul precursors requires a compatible snRNA promoter (19,36).…”
mentioning
confidence: 99%